2020
DOI: 10.1097/lbr.0000000000000610
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled Sedation During Flexible Bronchoscopy

Abstract: Background: Patient-controlled sedation (PCS) is a documented method for endoscopic procedures considered to facilitate early recovery. Limited data have been reported, however, on its use during flexible bronchoscopy (FB). Methods: This study hypothesized that PCS with propofol during FB would facilitate early recovery, with similar bronchoscopist and patient satisfaction compared with nurse-controlled sedation (NCS) with midazolam. A total of 150 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…Therefore, PCS is a cost-saving method for sedation during endoscopic procedures that can also improve procedure feasibility and patient satisfaction without affecting patient safety. 14,15 All procedures under PCS might not be possible to continue and require full anaesthesia to complete. With a bedside anaesthetic nurse and an anaesthesiologist immediately available, this can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, PCS is a cost-saving method for sedation during endoscopic procedures that can also improve procedure feasibility and patient satisfaction without affecting patient safety. 14,15 All procedures under PCS might not be possible to continue and require full anaesthesia to complete. With a bedside anaesthetic nurse and an anaesthesiologist immediately available, this can be accomplished.…”
Section: Discussionmentioning
confidence: 99%
“…The first study evaluated ERCP 14 and was conducted at the Surgical Clinic between January 2011 and May 2012. The second study examined bronchoscopy 15 and was conducted at the Department of Pulmonary Medicine between April 2016 and May 2017.…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Instead, we added 5 minutes for the start/preparation respectively completion/dismantling of the procedure (10 minutes in total) to the measured procedural time. Our main finding that PCS is a cost-saving method was primarily based on reduced costs for hospital stay and avoidance of aborted procedures that had to be The patients in both studies 3,4 had adequate and sufficient sedation upon insertion of endoscope and during the procedure. The post-procedural assessment by the patients using PCS in both studies showed significantly higher satisfaction of the procedure compared with patients administrated midazolam.…”
Section: Response Letter To the Editormentioning
confidence: 95%
“…BG, LN, LB, AN, and FS contributed substantially to the study design, cost analysis and interpretation, and writing of the manuscript. Benjamin Grossmann 1,2 Andreas Nilsson 2,3 Folke Sjöberg 1,4 Lars Bernfort 5 Lena Nilsson 2,3 1…”
Section: Auth O R Co Ntr I B Uti O Nmentioning
confidence: 99%